2018
DOI: 10.3389/fphys.2018.00885
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Extension and C-Terminal Domains Are Required for ABCB6/HMT-1 Protein Interactions, Function in Cadmium Detoxification, and Localization to the Endosomal-Recycling System in Caenorhabditis elegans

Abstract: The chronic exposure of humans to toxic metals such as cadmium from food and air causes dysfunction of vital organs, neurodegenerative conditions, and cancer. In this regard, members of the ABCB sub-family of the ATP-binding cassette (ABC) transporter superfamily, ABCB6/HMT-1, are acutely required for the detoxification of heavy metals and are present in genomes of many organisms including the nematode worm, Caenorhabditis elegans and humans. We showed previously that C. elegans ABCB6/HMT-1 detoxifies cadmium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
(139 reference statements)
2
11
0
Order By: Relevance
“…In C. elegans , ABCB6 was expressed under the control of the endogenous CeHMT-1 promoter, offering an opportunity to study ABCB6 localization in an intact organism without the burden of artifacts associated with overexpression. In complete agreement with a recent report [41], we find that CeHMT-1 is localized to the endosomal compartment in the intestinal cells of the nematode (Fig. 3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In C. elegans , ABCB6 was expressed under the control of the endogenous CeHMT-1 promoter, offering an opportunity to study ABCB6 localization in an intact organism without the burden of artifacts associated with overexpression. In complete agreement with a recent report [41], we find that CeHMT-1 is localized to the endosomal compartment in the intestinal cells of the nematode (Fig. 3).…”
Section: Discussionsupporting
confidence: 93%
“…3). Our results confirm recent studies establishing the relevance of the N-terminal domain in the localization of ABCB6 and CeHMT-1 [13, 41]. Determining the subcellular localization of a protein is a key step toward understanding the cellular function of a protein.…”
Section: Discussionsupporting
confidence: 91%
“…ATP‐driven translocation of porphyrin into mitochondria is severely impaired in the absence of ABCB6, 5 highlighting the role of ABCB6 in heme precursor translocation. Several studies have suggested that ABCB6 is also presented in other membrane systems like intracellular endo/lysosomal compartment 6–9 or the plasma membrane, 10 which is consistent with its ability to confer tolerance to toxic heavy metals 1,3 . ABCB6 has also been shown to protect cells from oxidative stress 11 and drug toxicity 12,13 .…”
Section: Introductionmentioning
confidence: 81%
“…In the ATPase hydrolysis assay, we observed stimulated ATPase activity in the presence of both Cu 2+ and GSH. Previous studies have shown that ABCB6 is involved in cell resistance to arsenic and cadmium, 3,9 most likely through GSH conjugation. Although our data did not show direct binding or stimulated ATPase activity of GSH for ABCB6, it cannot be ruled out that GSH may bind to ABCB6 with low affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results indicate that TMD0 is dispensable for the folding, dimerization, membrane insertion and ATP binding/hydrolysis of the core–ABCB6 complex, but has a crucial role in the lysosomal targeting of ABCB6 [108]. Almost identical results were obtained with CeHMT‐1 ( C. elegans Heavy Metal Tolerance factor 1), which shares significant sequence and topological similarity with ABCB6 [116,117]. The evolutionarily conserved role of the HMT‐1 proteins is to confer tolerance to heavy metals through the intracellular sequestration of metal complexes.…”
Section: The Enigmatic Abcb6 Transporter: a Journey Along The Endolysmentioning
confidence: 82%